İlişkide Karar Verme Ölçeğinin Türk Kültürüne Uyarlanması / The Turkish Adaptation of Relationship Deciding Scale - Tosun, Cansu; Yazıcı, Hikmet; Altun, Fatma (Journal of History Culture and Art Research, 2017)
Abstract The purpose of this study was to assess the validity and reliability of Relationship Deciding Scale (Vennum & Fincham, 2011) for Turkish culture. The sample of the study consisted of 880 students (EFA=439, CFA=441) studying at Karadeniz Technical University. Criterion-related validity, exploratory and confirmatory factor analyses were conducted for the validity of RDS while internal consistency, split half and test-retest techniques were performed to examine the reliability of RDS. Exploratory factor analysis (EFA) revealed that the scale had two-factor structures. However, two items were removed from the scale because they didn't have appropriate factor loadings. The scale consisting of 10 items explained 58.97% of the total variance. The results of confirmatory factor analysis (CFA) indicated that the model was compatible with the data. In the reliability analysis for EFA and CFA samples, Cronbach alpha coefficients were found as .87 and .86 respectively. Internal consistency coefficients of subscales were found as .83 and .80 for “Relationship Confidence”, .82 and .84 for “Directing Relationship”. According to test-retest reliability analysis results, the whole scale’s coefficient was r= .67. In addition, as a result of criterion validity analysis, correlations (r= .33) between Self-Control Scale (Duyan, Gülden & Gelbal, 2012) and Relationship Deciding Scale (RDS) were found to be statistically significant. In conclusion, these findings suggest that RDS, which has two-factor structures with 10 items, can be suggested as a valid and reliable instrument in Turkish culture. Öz Bu araştırmanın amacı, Vennum ve Fincham (2011) tarafından geliştirilen İlişkide Karar Verme Ölçeği’nin (Relationship Deciding Scale) Türk kültürüne uyarlanması ile ilgili geçerlik ve güvenirlik işlemlerini yapmaktır. Araştırma grubu Karadeniz Teknik Üniversitesi’nde öğrenim gören 880 öğrenciden (AFA=439, DFA=441) oluşmaktadır. İlişkide Karar Verme Ölçeği’nin (İKVÖ) geçerlik işlemlerinde, ölçüt bağıntılı geçerlik, açımlayıcı ve doğrulayıcı faktör analizi, güvenirlik işlemlerinde ise iç tutarlılık, testi yarıya bölme ve testin tekrarı tekniklerinden yararlanılmıştır. Yapılan açımlayıcı faktör analizi (AFA) sonucunda ölçeğin iki faktörlü yapı gösterdiği ortaya çıkmıştır. Uygun faktör yüklerine sahip olmadıkları için iki madde modelden çıkarılmıştır. 10 maddeden oluşan ölçek toplam varyansın %58.97’sini açıklamıştır. Doğrulayıcı faktör analizli sonuçları (DFA) verinin modele iyi uyum sağladığını göstermiştir. AFA ve DFA örneklemleri için yapılan güvenirlik analizlerinde, Cronbach alfa iç tutarlılık kat sayıları sırasıyla .87 ve .86 olarak bulunurken alt ölçekler için bulunan iç tutarlılık kat sayıları ise “İlişkide Kendine Güven” için .83 ve .80, “İlişkiyi Yönetme” için .82 ve .84’tür. Ölçeğin test tekrar test güvenirliğinin r= .67 olduğu tespit edilmiştir. Ayrıca ölçüt geçerliği kapsamında yapılan analizler sonucunda Öz Denetim Ölçeği (Duyan, Gülden ve Gelbal, 2012) ile İKVÖ arasında .33 değerinde beklenen yönde bir ilişki saptanmıştır. Bu çalışma sonucunda İKVÖ’nün Türk kültüründe geçerli ve güvenilir bir ölçme aracı olduğu değerlendirilmektedir.